Pattern synthesis of linear array antennas based on Chaos Triangular Pelican Optimization Algorithm - Anyong Liu; Yan Liu; Zhuo Chen; Yibo Wang; Yurong Yin (Scientific Reports)
Abstract In wireless communication systems, array antennas with high gain and low sidelobe performance can enhance the system’s signal processing and anti-interference capabilities, using intelligent optimization algorithm to optimize the performance of array antenna can achieve this goal. This article proposes an optimization algorithm called Chaos Triangular Pelican Optimization Algorithm (CTPOA), which combines Logistic chaotic mapping initialization and triangle walk strategy with original Pelican Optimization Algorithm (POA). The results of eight test functions show that CTPOA is quite excellent in both convergence and optimization ability. In addition, we also applied CTPOA for the first time to design the pattern synthesis of linear array antennas (LAA). According to the simulation results of four designed LAA, CTPOA also has excellent performance in antenna optimization. From this, it can be seen that the CTPOA proposed in this article has a certain position in the field of optimization.